2020
DOI: 10.3390/cancers12092494
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Therapies for Melanoma

Abstract: The incidence of cutaneous malignant melanoma (CMM) is significantly increasing worldwide.[...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Intracellular signaling through KIT plays a critical role in melanocyte development. For the last ten years, it has had an emerging role as an oncogene and therapeutic target in melanoma 62–64 . KIT mutations are found in only 3% of all melanomas but a disproportionate amount of KIT aberrations has been identified in melanoma arising from chronically sun‐damaged skin in acral and mucosal tissue; the N566D mutation being among the most commonly found in this gene 65,66 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular signaling through KIT plays a critical role in melanocyte development. For the last ten years, it has had an emerging role as an oncogene and therapeutic target in melanoma 62–64 . KIT mutations are found in only 3% of all melanomas but a disproportionate amount of KIT aberrations has been identified in melanoma arising from chronically sun‐damaged skin in acral and mucosal tissue; the N566D mutation being among the most commonly found in this gene 65,66 .…”
Section: Resultsmentioning
confidence: 99%
“…For the last ten years, it has had an emerging role as an oncogene and therapeutic target in melanoma. [62][63][64] KIT mutations are found in only 3% of all melanomas but a disproportionate amount of KIT aberrations has been identified in melanoma arising from chronically sun-damaged skin in acral and mucosal tissue; the N566D mutation being among the most commonly found in this gene. 65,66 KIT mutations are nearly always mutually exclusive with NRAS or BRAF and thus define a unique subtype of melanoma.…”
Section: Identification Of Melanoma Protein Mutationsmentioning
confidence: 99%
“…Despite remarkable progress in CMM-targeted therapy and immunotherapy, the metastatic disease represents a therapeutic challenge and leaves patients with an uncertain prognosis (Smetana et al 2020 ). From this perspective, identification of new therapeutic targets is critical to manage CMM successfully (Brustugun et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous X-ray crystallographic studies have shown that imatinib can bind to the inactive conformation of c-KIT, further validating this hypothesis [ 151 ]. FGF2 is a growth factor shown to induce resistance to nilotinib, a second-generation drug of the imatinib family, likely through activation of the MAPK pathway [ 158 , 159 ]. Ponatinib is a multi-target TKI previously approved to treat chronic myeloid leukemia (CML) caused by BCR-ABL fusion.…”
Section: C-kitmentioning
confidence: 99%